Ammonium Is toxic for aging yeast cells, inducing death and shortening of the chronological lifespan - Santos, Júlia (2012)
Here we show that in aging Saccharomyces cerevisiae (budding yeast) cells, NH4+ induces cell death associated with shortening of chronological life span. This effect is positively correlated with the concentration of NH4+ added to the culture medium and is particularly evident when cells are starved for auxotrophy-complementing amino acids. NH4+-induced cell death is accompanied by an initial small increase of apoptotic cells followed by extensive necrosis. Autophagy is inhibited by NH4+, but this does not cause a decrease in cell viability. We propose that the toxic effects of NH4+ are mediated by activation of PKA and TOR and inhibition of Sch9p. Our data show that NH4+ induces cell death in aging cultures through the regulation of evolutionary conserved pathways. They may also provide new insights into longevity regulation in multicellular organisms and increase our understanding of human disorders such as hyperammonemia as well as effects of amino acid deprivation employed as a therapeutic strategy.